2018
DOI: 10.3892/mmr.2018.8885
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of casein kinase 2 inhibits PKC‑induced cell invasion by targeting MMP‑9 in MCF‑7 cells

Abstract: Casein kinase 2 (CK2) is a serine/threonine protein kinase that has been considered to represent an important factor in mammary tumorigenesis. Increased expression of matrix metalloproteinase‑9 (MMP‑9) via nuclear factor‑κB (NF‑κB) activation has been demonstrated to promote breast cancer cell invasion. In the present study, the involvement of CK2 in protein kinase C (PKC) induced cell invasion in MCF‑7 breast cancer cells was investigated as well as the underlying molecular mechanisms. The mRNA and protein le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…In this work, we have shown that the apigenin upregulation of functional CD26/DPPIV at the cell surface of intestinal epithelial cells (a) is consistent across multiple well‐differentiated human cell lines, (b) is due to cellular redistribution rather than a change in expression, (c) may be reproduced by multiple inhibitors of CK2 kinase activity, (d) does not involve downregulation of CK2 protein, and (e) is abrogated by siRNA knockdown of available CK2. It is well established that apigenin can inhibit CK2 activity, and indeed, it is used experimentally as a CK2 inhibitor (Ahmad, Wang, & Ahmed, 2006; Jung, Kim, & Lee, 2014; Kim et al., 2018; Kroonen et al., 2012; Suhas et al., 2018). We conclude that the ability of apigenin to upregulate CD26/DPPIV involves inhibition of the kinase activity of CK2 and is dependent upon the presence of functional CK2 enzyme.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this work, we have shown that the apigenin upregulation of functional CD26/DPPIV at the cell surface of intestinal epithelial cells (a) is consistent across multiple well‐differentiated human cell lines, (b) is due to cellular redistribution rather than a change in expression, (c) may be reproduced by multiple inhibitors of CK2 kinase activity, (d) does not involve downregulation of CK2 protein, and (e) is abrogated by siRNA knockdown of available CK2. It is well established that apigenin can inhibit CK2 activity, and indeed, it is used experimentally as a CK2 inhibitor (Ahmad, Wang, & Ahmed, 2006; Jung, Kim, & Lee, 2014; Kim et al., 2018; Kroonen et al., 2012; Suhas et al., 2018). We conclude that the ability of apigenin to upregulate CD26/DPPIV involves inhibition of the kinase activity of CK2 and is dependent upon the presence of functional CK2 enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is not certain that apigenin influences cellular behaviors, including regulation of interactions with the extracellular matrix, cellular contractility, and the levels of molecules including CD26/DPPIV (Kim et al., 2018; Lefort & Blay, 2011; Suhas et al., 2018), solely through inhibition of CK2. The effects of apigenin in cellular experimental systems are distinct from synthetic CK2 inhibitors such as CX‐4945 (Suhas et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations